The academic writing of university english learners: a corpus-based study - Guedes, Annallena de Souza (Revista do SELL, 2016)
This article discusses and analyzes the frequency and use of high - frequency verbs in argumentative essays written by Brazilian English learners of Federal University of Minas Gerais. We used Corpus Linguistic (CL) tools to analyze the grammar patterns found on data of texts produced by the learners enrolled in English for Academic Purposes subject (Inglês para Fins Acadêmicos- IFA). We listed the ten most frequent verbs and we decided to analyze the use of make and get and outline their fifteen most frequent collocates. The results showed that there are some difficulties on the appropriate use of these verbs, especially when it turns to collocations, as well as there is a tendency of patterns use interference of their native language.